Theory and Diagnosis of Consumer Behavior in Tourism and Destination Branding: The Meaning of Sustainability for Tourists - Liu Yabing; Uehara Noriko; Takahashi Akio (Journal of Japan Management Diagnosis Association, 2024)
Since the onset of the COVID-19 pandemic, awareness of green living, which involves a more local and environmentally conscious lifestyle, has been increasing, particularly among the affluent. This shift in consciousness is reflected in consumer behavior across various fields. In the tourism sector, there is a growing interest in sustainable travel that reduces environmental impact and considers the local communities of destination areas. This paper aims to examine overseas efforts in sustainable tourism and the changing awareness of travelers since the COVID-19 pandemic. Furthermore, it seeks to consider destination branding strategies in post-COVID Japan. コロナ禍以降，よりローカルで環境に配慮するグリーンリビング（環境に良い暮らし）への意識が富裕層を中心に高まっている。こうした意識の変化はさまざまな分野の消費者行動に反映されるが，観光分野では，環境負荷を減らし，旅先の地域社会に配慮するサステナブルな旅が注目を集めている。本稿は，サステナブル・ツーリズムに関する海外の取り組みとコロナ禍以降の旅行者意識の変化に考察を加え，アフターコロナの日本におけるデスティネーション・ブランディング戦略に関して検討することを目的とするものである。